A reflection across the x-axis has the rule:
(x,y)→(x,-y).
Then:
- A(-1,-1)→A'(-1,1),
- B(0,1)→B'(0,-1),
- C(4,2)→C'(4,-2),
- D(6,0)→D'(6,0),
- E(3,-3)→E'(3,3).
Answer: the vertices of the image are A'(-1,1), B'(0,-1), C'(4,-2), D'(6,0) and E'(3,3).
Step 1: begin by writing the formula for slope intercept form
step2: substitute the given slope for X
step3: use the order pair you given (x,y) and substitute these values for the variables x and y in the equation
step4: solve for y ( y-intercept of the graph)
step5: rewrite the original equation in step 1 substituting the slope for x and the y-intercept for y
Answer:
- equation: y = x+3
- inequality: y < x+3
Step-by-step explanation:
The slope of the line is 1 unit of rise for 1 unit of run, so ...
m = rise/run = 1/1 = 1
The y-intercept is 3 grid lines above the x-axis, so is (0, 3).
Then the equation of the line is ...
y = 1x +3
The inequality has that line as a boundary, but the y-values on the line are not part of the solution space. Only y-values below the line (less than those on the line) are in the solution. The inequality is ...
y < x +3
Answer:
Step-by-step explanation:
v=4pi*r^3/3=3052.08
4*3.14/3*r^3=3052.08
4.2*r^3=3052.08
r^3=3052.08/4.2=726.7
so r ≈9
Answer: 6
Step-by-step explanation: Gets x by itself.